Pemantauan Jumlah Batang Eucalyptus pellita Umur 6 Bulan Berdasarkan Hasil Foto Drone - Sugeng Wahyudiono; Tatik Suhartati; Yudi (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2023)
The use of unmanned aircraft (UAV) or drones, apart from being used for mapping, can be a solution for quickly obtaining information and carrying out forest inventories with very detailed resolution results. Plantation Monitoring Assessment (PMA) aged 6 months is an initial inventory activity, later the data from PMA 6 will be the basic data for subsequent PMA. So, with drones, it is hoped that satisfactory results will be obtained. Apart from that, drones can be used to count the number of live and dead trees as well as empty spots. This research aims to compare the results of tree calculations directly in the field with the results of drone photos. This research was carried out on 6 month old Eucalyptus pellita plants in compartment A034, Baserah Sector, PT. RAPP. Data collection was carried out using systematic random sampling with a sampling intensity of 1%. The data taken is in the form of data on the number of live and dead/empty plants in the field and photographed with a drone. The test was carried out to test the differences in the number of dead/empty plants directly in the field and calculations using drone photos, namely the t test. The results showed that there was no difference between the number of live and dead/empty plants in the field and from drone photos.